Fast Determination of β-estradiol by Chromatographic Method and its Application to Clinical Pharmacokinetics Studies - Hefnawy, Mohammed; Mohamed, Moustafa; Alanazi, Amer; Attia, Sabry; Mostafa, Gamal Abdel-Hafiz (Current Pharmaceutical Analysis, 2016)
In this clinical study, a fast chromatographic (HPLC) method has been established for the quantification of β-estradiol. β-estradiol and the IS (verapamil) were separated from plasma using the deproteinisation procedure, followed by injection of the clear solution of the supernatant into the chromatographic system. For the first time, the proposed method employed a monolithic column in the analysis. The analyte was eluted on a monolithic stationary phase column with a carrier composition of phosphate buffer: acetonitrile (pH 3.5) (90: 10, v/v) at a flow rate of 2.0 mL / min. The target drugs were detected at 280 and 310 nm for fluorescence signal. The proposed method showed a calibration graph over 5 - 1000 ng/ mL, with a low concentration of 1.5 ng/mL. The approach was statistically agreed as regards linearity, accuracy, precision, selectivity and stability according to the FDA criteria. The precision of the method as the intraand inter-day study variation did not exceed 3.0 % from the nominal concentration. The accuracy of β-estradiol was observed to be within ±12% of the theoretical value. The method was good applied to mice plasma.
Keywords: monolithic silica column